Necessary steps to accelerate the integration of wearable sensors into recreation and competitive sports - Düking, P.; Stammel, C.; Sperlich, B.; Sutehall, S.; Muniz-Pardos, B.; Lima, G.; Kilduff, L.; Keramitsoglou, I.; Li, G.; Pigozzi, F.; Pitsiladis, Y. P. (Current Sports Medicine Reports, 2018)
A variety of wearable sensor technologies (herein referred to as ``wearables``) are being developed by an ever-increasing number of companies and receiving considerable attention from the athletic community. Wearables can be defined as small, lightweight devices worn on, close to, or even in the body where they monitor, analyze, transmit, and/or receive data from other devices and/or cloud services to provide biofeedback in real time to the user (1). Wearables can be used by a wide range of individuals engaged in activities of daily living or training and competing as amateur or professional athletes. Wearables may be used to monitor and analyze physiological parameters and individualize training programs to enhance performance and/or health (2Y4). Pedometers were among the first wearables developed to measure physical activity by the polymath Leonardo da Vinci some 500 years ago (5). da Vinci`s mechanism was designed to measure vertical movements by moving a lever up and down, resulting in the rotation of a gear and this remains the basis of modern day devices. Major advances in technology over the past two decades have resulted in the triaxial accelerometer that measures movements in the anteroposterior, mediolateral, and vertical direction, alleviating the limitations of previous devices (6). Accelerometry-based wearables can be used to objectively assess physical activity and interventions aimed at improving health-related outcomes